Digital Female Representation Subjectivity in Her (2013): Postfeminist Perspective Analysis: English - Viki Savira Nasyarin; Yoga Sudarisman; Erlan Aditya Ardiansyah (Prodi Tadris Bahasa Inggris, 2025)
This study examines the representation of female subjectivity in the film Her (2013) through a postfeminist perspective. The film, directed by Spike Jonze, presents Samantha, an artificial intelligence, as a character who challenges traditional gender roles and offers a new lens through which to explore female identity in the digital age. It used a qualitative method, where dialogue, character actions, and interactions between Theodore and Samantha are analyzed to understand the representation of postfeminism in their relationship. By focusing on key themes such as freedom, gender relations, and identity formation, this study employs postfeminist representation of Helene Cixous and Judith Butler, to interpret Samantha’s role in transcending traditional gender constraints. The findings describe that Her (2013) postfeminist representation of female identity, where technology and emotional growth intersect, offering a critique of conventional gender norms. Her (2013) Samantha's journey highlights the identity, the film's critique of societal gender norms and its portrayal of a fluid, dynamic female identity that aligns with modern perspectives on empowerment and self discovery. Cixous advocates for women to actively participate in their liberation by